Persepsi Mahasiswa Terhadap Kebijakan MBKM dan Relevansi Kurikulum - Gunarsa, I Komang Gede Raditya; Narsa, Niluh Putu Dian Rosalina Handayani; Narsa, I Made; Sedianingsih (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This study aims to examine the perception of accounting undergraduate students at Universitas Airlangga regarding MBKM policies, curriculum relevance, and study program readiness in implementing the MBKM program. Furthermore, this study also examines the effect of students' perception on interest in joining in the MBKM program. This study used a survey method with a population of all accounting undergraduate students (2019, 2020, and 2021) at Universitas Airlangga  The number of final respondents is 275. The data analysis technique used multiple regression analysis. The results showed that students' perceptions of MBKM policies, curriculum relevance and study program readiness to implement MBKM were quite high (with an average answer above five out of a scale of seven). This study also succeeded in proving that student perceptions of MBKM policies and student perceptions of study program readiness in implementing MBKM have a positive effect on student interest in participating in MBKM. However, it failed to prove the second hypothesis related to the effect of students' perceptions of the relevance of the accounting curriculum on interest in joining MBKM. Suggestions for further research can be extended to all Airlangga University students so that they can provide more comprehensive input on the MBKM program.